Endoscopy-related injury among gastroenterology trainees - Pawa, Swati; Martindale, Sarah L.; Gaidos, Jill K.J.; Banerjee, Promila; Kothari, Shivangi; D’Souza, Sharlene L.; Oxentenko, Amy S.; Burke, Carol A. (Endoscopy International Open, 2022)
Background and study aims Endoscopy-related injury (ERI) is widespread among practicing gastroenterologists. However, less is known about the incidence among trainees. This study assesses the rate of self-reported ERI occurrence, patterns of injury, and knowledge of preventive strategies in a nationally representative sample of gastroenterology fellows.Methods A 38-item electronic survey was sent to members of the American College of Gastroenterology. One hundred and sixty-eight gastroenterology fellows were included in analyses. Descriptive and univariate analyses evaluated the likelihood of ERI by workload parameters and gender.Results ERI was reported by 54.8 % of respondents. ERI was most common in the thumb (58.7 %), hand/finger (56.5 %), and wrist (47.8 %). There was no significant difference in the reported occurrence of ERI between male and female gastroenterology fellows. However, female fellows were significantly more likely to report a greater number of body areas affected by ERI, and male fellows were more likely to report elbow pain. Most respondents (85.1 %) reported discussion about, or training in, ergonomic strategies during gastroenterology fellowship.Conclusions ERI is reported to occur as early as gastroenterology fellowship. Results of this study support this finding and highlight the need for ongoing implementation and monitoring of a formal ergonomics training program as well as development of ergonomically appropriate instruments. Implications of these findings likely extend to trainees in other procedural related specialties like orthopedics and general surgery, though further research is required. Ergonomics training in gastroenterology fellowship and monitoring of its impact on trainees reported ERI is important due to negative effects on productivity and career longevity.